Administering probiotic yakult + tape yeast into the mixture of rice and corn bran as partial replacement of commercial diet affects the carcass yield of broiler chickens - Zulfan Zulfan; Herawati Latif; Muhammad Aman Yaman; Cut Aida Fitri; Muhammad Haris Munandar (Faculty of Animal Science, Universitas Brawijaya, 2021)
The residue originated from antibiotics and hormones had been thought to carry out adverse effects for the human who consume meat processed from the broilers treated by antibiotic feed additive. For this reason, using an alternative additive such as probiotic might produce healthier meat. The objective of the recent study was to evaluate administering different levels of probiotic yakult + tape yeast (YTy) into the mixing of rice bran + corn bran (RCB) to replace 30% of the commercial diet to carcass yield and abdominal fat of broilers. As many as 100 broiler chicks, Cobb strain, were reared up to 5 weeks in this study. The study was designed into a Completely Randomized Design with subsampling consisted of 5 treatments, 4 replications, and 2 sub samples. Broiler commercial diet with the market code of CP 511 Hi-provite manufactured by PT Charoen Pokphand was used for a positive control diet (P0+). The RCB feeds were mixed with 0, 10, 20, and 30 ml/kg of probiotic YTy then being used to replace 30% of the commercial diet to build experimental diets P0-, P1, P2, and P3, respectively. The results of the recent study indicated that administering 10‒30 ml/kg of probiotic YTy highly significantly (P<0.01) increased the weights of the whole carcass and carcass parts. The percentages of whole carcasses among P1, P2, and P3, however, were not statistically different. The percentage of the breast significantly (P<0.05) increased while the percentage of the back significantly (P<0.05) decreased. Although statistically not significant differences, the abdominal fat percentage tended to decline. In conclusion, administering a probiotic YTy in the diet increased the percentage of the whole carcass and tended to reduce the abdominal fat of the broiler.